The UN voluntary compact and peacekeeping abuse: assessing a soft law solution for sexual exploitation and abuse. Issue 3 (16th March 2023) - Comstock, Audrey L.
ABSTRACT: In 2017, to address the increasingly visible and prevalent occurrence of peacekeeper sexual exploitation and abuse (SEA) of civilians under their protection, the UN Secretary-General created a Voluntary Compact on state behaviour. As of 2020, 103 states signed the agreement. Building on the robust literatures of human rights law, sexual abuse, and conflict, I examine whether signing the Voluntary Compact has any relationship with the levels of reported abuse, punishing accused SEA perpetrators, and funding victim relief efforts. Through quantitative analysis of annual reports of reports of SEA and punishment actions from the UN Conduct in Field Missions unit 2007–2019, I find that Troop Contributing Countries that signed were more likely to issue national-level punishments in cases of severe abuse and to contribute to victim funding. However, there is not a clear finding of any reduction of reported abuse following signature. I conclude by discussing the Voluntary Compact as a mixed-success story for soft international law so far. Given its lack of teeth, this finding is important as the UN and other international organisations continue to prevent and punish peacekeeper SEA and use nonbinding international law.